2022
DOI: 10.3390/jpm12060990
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of All-Cause Mortality Following Percutaneous Coronary Intervention in Bifurcation Lesions Using Machine Learning Algorithms

Abstract: Stratifying prognosis following coronary bifurcation percutaneous coronary intervention (PCI) is an unmet clinical need that may be fulfilled through the adoption of machine learning (ML) algorithms to refine outcome predictions. We sought to develop an ML-based risk stratification model built on clinical, anatomical, and procedural features to predict all-cause mortality following contemporary bifurcation PCI. Multiple ML models to predict all-cause mortality were tested on a cohort of 2393 patients (training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…There have been some mid‐ to long‐term studies on the prognosis according to lesion length in patients with CTO lesion, and it has been reported that lesion length is associated with adverse clinical outcomes such as revascularization and MACE 19,20 . However, including our previous study, none of the studies on lesion length and long‐term prognosis of CTO can demonstrate a correlation between hard endpoints such as cardiac mortality and lesion length 20–22 . In addition, in the most recently reported multicenter study on the relationship between lesion length and clinical outcomes, the cut‐off for the length of the lesion was set at 20 mm, and the study only reported the association between lesion length and in‐hospital or periprocedural outcomes 23 .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…There have been some mid‐ to long‐term studies on the prognosis according to lesion length in patients with CTO lesion, and it has been reported that lesion length is associated with adverse clinical outcomes such as revascularization and MACE 19,20 . However, including our previous study, none of the studies on lesion length and long‐term prognosis of CTO can demonstrate a correlation between hard endpoints such as cardiac mortality and lesion length 20–22 . In addition, in the most recently reported multicenter study on the relationship between lesion length and clinical outcomes, the cut‐off for the length of the lesion was set at 20 mm, and the study only reported the association between lesion length and in‐hospital or periprocedural outcomes 23 .…”
Section: Discussionmentioning
confidence: 71%
“…19,20 However, including our previous study, none of the studies on lesion length and long-term prognosis of CTO can demonstrate a correlation between hard endpoints such as cardiac mortality and lesion length. [20][21][22] In addition, in the most recently reported multicenter study on the relationship between lesion length and clinical outcomes, the cut-off for the length of the lesion was set at 20 mm, and the study only reported the association between lesion length and in-hospital or periprocedural outcomes. 23 However, in this study, unlike the results of recent studies that evaluated the role of lesion length on clinical outcomes, the incidence of hard endpoints such as cardiac mortality and mortality were also found to be frequent in long lesions.…”
Section: Cto Lesions Have Different Features Than Non-cto Lesions Inmentioning
confidence: 99%